STRATEGI PENGEMBANGAN PEMASARAN PRODUK AGRIBISNIS ES PISANG IJO RAJA (Product Marketing Development Strategy of â€œEs King Banana Greenâ€ Agribusiness ) - Clerry Nathania Lungari; Ribka M. Kumaat; Celcius Talumingan (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2021)
This study aims to determine the marketing strategy used by the